Bonding Conductive Paste
A bonding conductive paste with silver particles and a specific solvent formulation addresses issues of waste, conductivity, and viscosity, enabling high-precision and strong bonding for electronic devices.
Patent Information
- Application Number
- JP2021537313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-07
- Filing Date
- 2020-08-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-08-04
AI Technical Summary
Existing methods for forming conductive wiring and bonding structures for electronic devices face issues such as waste generation, poor conductivity due to non-conductive components, oxidation of substrates, and viscosity fluctuations in conductive pastes, making it difficult to achieve high-precision and strong bonding.
A bonding conductive paste containing silver particles with specific size distributions and a solvent represented by formula (I) is used, which allows for even printing and quick sintering in an inert gas atmosphere, eliminating the need for adhesives and ensuring high bonding strength and precision.
The paste enables the formation of high-precision conductor wiring and bonded structures with excellent electrical properties and bonding strength, preventing viscosity fluctuations and substrate deterioration during the printing and sintering processes.
Smart Images

Figure 0007609781000001 
Figure 0007609781000002 
Figure 0007609781000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a bonding conductor paste used for forming conductor wiring and bonded structures for connecting electronic elements such as power semiconductor elements and LED elements. This application claims priority from Japanese Patent Application No. 2019-145510, filed in Japan on August 7, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] When mounting electronic elements such as power semiconductor elements and LED elements, it is necessary to bond multiple materials with high strength, and for this purpose, conductor wiring, bonding structures, and wiring boards equipped with these are used.
[0003] As a method for forming the conductor wiring, for example, a method for manufacturing copper wiring by etching a copper foil attached to an insulating substrate is known, but this method has a problem in that a large amount of waste is generated by etching.
[0004] Another known method is to apply a conductor paste containing conductive particles and an adhesive onto an insulating substrate by printing or the like, and then sinter the paste to produce conductor wiring (Non-Patent Document 1). The conductor paste containing the adhesive has an appropriate viscosity, so it can be printed with high precision, and wiring is produced by sintering the paste. However, the adhesive and adhesive-derived components, which are non-conductive components, remain after sintering, hindering interactions between conductive particles and between the conductive particles and the substrate, making it difficult to obtain good conductivity.
[0005] Patent Document 1 describes that the use of a conductor paste containing no adhesive or thickener, obtained by mixing silver particles having an average particle size (median diameter) of 0.1 μm to 15 μm with an alcohol solvent (methanol, ethanol, or ethylene glycol), suppresses the residual non-conductive components after sintering and reduces the electrical resistance value. However, copper and nickel substrates and wiring not protected by plating in semiconductor modules are easily oxidized by oxygen and need to be sintered under an atmosphere of inert gas such as nitrogen. However, with a conductor paste containing silver particles having an average particle size of 0.1 μm or more, sintering does not proceed under a nitrogen atmosphere, making it difficult to bond. In addition, the conductor paste using the alcohol solvent is prone to "bleeding," and furthermore, since methanol and ethanol have a high volatilization rate at the printing temperature, the viscosity of the conductor paste using these is prone to fluctuating during printing, making it difficult to form a fine pattern with high accuracy. Another problem with the conductor paste using ethylene glycol is that it is difficult to obtain conductor wiring with excellent bonding strength with the substrate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-170277 A [Non-patent literature]
[0007] [Non-Patent Document 1] Yi Li, CP Wong, "Recent advances of conductive adhesives as a lead-free alternative in electronic packaging: Materials, processing, reliability and applications", Materials Science and Engineering, 2006, R51, p1-35 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, an object of the present disclosure is to provide a bonding conductor paste for forming conductor wiring and bonded structures for connecting electronic elements on a substrate by a printing method or the like, which can suppress fluctuations in viscosity at printing temperatures to allow for even printing, and which can be sintered quickly even in an inert gas atmosphere such as nitrogen to form high-precision conductor wiring and bonded structures that can connect a substrate and electronic elements with high bonding strength. [Means for solving the problem]
[0009] The inventors of the present disclosure have conducted intensive studies to solve the above problems, and have found that when silver particles having an average particle size (median size) of less than 0.1 μm (100 nm) are mixed with silver particles having an average particle size (median size) of 0.1 μm or more, the mixture can be sintered quickly even under an inert gas atmosphere such as nitrogen to form a highly accurate conductor wiring or bonded structure capable of connecting a substrate and an electronic element with high bonding strength. Furthermore, the inventors have found that a paste containing a compound represented by the following formula (I) as a solvent and containing silver particles having the above two different particle sizes as conductive particles has a viscosity suitable for printing without the addition of a thickener, can be printed without bleeding, the compound represented by the formula (I) is not easily volatilized at printing temperatures, and a paste containing the compound represented by the formula (I) as a solvent can suppress viscosity fluctuations during printing, can be printed without unevenness, and can form a sintered body with excellent conductivity even at low temperatures. The invention of the present disclosure has been completed based on these findings.
[0010] That is, the present disclosure provides a bondable conductor paste for forming a conductor wiring and / or a bonded structure for connecting electronic elements, the bondable conductor paste comprising conductive particles and a solvent, the conductive particles including silver particles (A) having an average particle diameter of 1 nm or more and less than 100 nm and silver particles (B) having an average particle diameter of 0.1 μm or more and 10 μm or less, The silver particles (A) are silver nanoparticles whose surfaces are coated with a protective agent containing an amine, As a solvent, R a -O-(XO) n -R b (I) (In the formula, R a represents a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. X represents a divalent group selected from a hydrocarbon group having 2 to 6 carbon atoms. R b R represents a hydrogen atom or a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. a and R b may be the same group. n represents an integer of 1 to 3. The present invention provides a bonding conductor paste comprising a compound (C) represented by the following formula:
[0011] The present disclosure also provides the above-mentioned bonding conductor paste, wherein a proportion of silver particles (A) in all silver particles contained in the bonding conductor paste is 50% by weight or less.
[0012] The present disclosure also provides a method for producing a protective agent in the silver particles (A), the protective agent comprising, as an amine, an aliphatic hydrocarbon monoamine (1) which comprises an aliphatic hydrocarbon group and one amino group, and in which the total number of carbon atoms in the aliphatic hydrocarbon group is 6 or more, The present invention further provides a bonding conductor paste comprising at least one of an aliphatic hydrocarbon monoamine (2) consisting of an aliphatic hydrocarbon group and one amino group, the total number of carbon atoms in the aliphatic hydrocarbon group being 5 or less, and an aliphatic hydrocarbon diamine (3) consisting of an aliphatic hydrocarbon group and two amino groups, the total number of carbon atoms in the aliphatic hydrocarbon group being 8 or less.
[0013] The present disclosure also provides the above bondable conductor paste, wherein the compound (C) represented by formula (I) has a boiling point of 160° C. or higher under normal pressure.
[0014] The present disclosure also provides the SP value [(cal / cm 3 ) 1 / 2 The adhesive conductor paste has a bonding strength of 8.6 or less.
[0015] The present disclosure also provides the above-mentioned bondable conductor paste, wherein X in formula (I) is an ethylene group, a propylene group or a trimethylene group.
[0016] The present disclosure also provides the above bonding conductor paste, wherein the total content of the silver particles (A) and the silver particles (B) in the total amount of the bonding conductor paste is 50 to 99.8 wt %.
[0017] The present disclosure also provides the above-mentioned bonding conductor paste, wherein the content of the organic component is 15% by weight or less relative to the bonding conductor paste (100% by weight).
[0018] The present disclosure also provides a method for producing an electronic component, comprising the steps of applying the above-mentioned bonding conductor paste onto a substrate and then sintering the paste to form a conductor wiring and / or a bonding structure. Effect of the Invention
[0019] The bondable conductor paste of the present disclosure contains two types of silver particles having different particle sizes, namely, silver particles (A) having an average particle size of 1 nm or more and less than 100 nm, and silver particles (B) having an average particle size of 0.1 μm or more and 10 μm or less, as conductive particles, and can be sintered quickly even under an inert gas atmosphere such as nitrogen to form a highly accurate conductor wiring or bonded structure that can connect a substrate and an electronic element with high bonding strength. Furthermore, since the paste contains a compound (C) represented by formula (I) as a solvent in addition to the silver particles (A) and (B), the paste has a viscosity suitable for a printing method, is less likely to bleed, and can form a highly accurate wiring pattern or bonded structure pattern by a printing method. In addition, there is no need to add an adhesive to increase viscosity, and although there was a problem in the past that electrical properties were reduced due to non-conductive components derived from the adhesive remaining after sintering, the paste can prevent the reduction in electrical properties due to the remaining non-conductive components, and can form a conductor wiring or bonded structure with excellent electrical properties. Furthermore, since the bonding conductor paste of the present disclosure uses compound (C) represented by formula (I) as a solvent, which is not easily volatilized at printing temperatures, the viscosity can be maintained constant during printing, enabling uniform, high-precision printing. Furthermore, the bonding conductor paste of the present disclosure can form conductor wiring and bonded structures with excellent bonding strength to substrates even when sintered at lower temperatures, and can reduce deterioration or damage to substrates, etc. due to sintering. Therefore, by using the bonding conductor paste of the present disclosure, conductor wiring and bonded structures with excellent bonding strength can be formed with high precision by a printing method, and a substrate and an electronic element can be strongly bonded via the conductor wiring and bonded structures, thereby making it possible to manufacture electronic components with excellent electrical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] (solvent) The bondable conductor paste of the present disclosure contains, as a solvent, one or more compounds (C) represented by the following formula (I). R a -O-(XO) n -R b (I)
[0021] In formula (I), R a represents a monovalent group selected from hydrocarbon groups and acyl groups having 1 to 6 carbon atoms. R a In the above formula, examples of the hydrocarbon group having 1 to 6 carbon atoms include monovalent groups selected from aliphatic hydrocarbon groups having 1 to 6 carbon atoms and alicyclic hydrocarbon groups having 3 to 6 carbon atoms. Examples of the monovalent aliphatic hydrocarbon group having 1 to 6 carbon atoms include linear or branched alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, s-butyl, t-butyl, pentyl, isopentyl, hexyl, and isohexyl groups; alkenyl groups having 2 to 6 carbon atoms, such as vinyl, allyl, and 1-butenyl groups; and alkynyl groups having 2 to 6 carbon atoms, such as ethynyl and propynyl groups. Examples of the monovalent alicyclic hydrocarbon group having 3 to 6 carbon atoms include cycloalkyl groups, such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl groups.
[0022] R aExamples of the acyl group (RCO- group) in the formula include acyl groups in which R is a linear or branched alkyl group having 1 to 10 carbon atoms (preferably 1 to 5 carbon atoms) (e.g., acetyl group, propionyl group, butyryl group, isobutyryl group, pivaloyl group, etc.).
[0023] In formula (I), X represents a divalent group selected from hydrocarbon groups having 2 to 6 carbon atoms. The hydrocarbon group having 2 to 6 carbon atoms for X includes a divalent group selected from aliphatic hydrocarbon groups having 2 to 6 carbon atoms and alicyclic hydrocarbon groups having 3 to 6 carbon atoms. Examples of the divalent aliphatic hydrocarbon group having 2 to 6 carbon atoms include an ethylene group (-CH 2 -CH 2 -), propylene group (-CH(CH 3 )CH 2 -), trimethylene group (-CH 2 -CH 2 -CH 2 Examples of the divalent alicyclic hydrocarbon group having 3 to 6 carbon atoms include cycloalkylene groups such as 1,2-cyclopentylene, 1,3-cyclopentylene, 1,2-cyclohexylene, 1,3-cyclohexylene, and 1,4-cyclohexylene. In the present disclosure, X is preferably an aliphatic hydrocarbon group having 2 to 6 carbon atoms, more preferably a linear or branched alkylene group having 2 to 6 carbon atoms, and even more preferably an ethylene group, a propylene group, or a trimethylene group.
[0024] In formula (I), R b represents a hydrogen atom or a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. The monovalent group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an acyl group includes the above R a Examples similar to those in R b is R a may be the same group as or different from.
[0025] n represents an integer of 1 to 3. n is preferably 2 or 3.
[0026] The number of carbon atoms constituting the compound (C) represented by formula (I) is preferably 8 to 13, and more preferably 10 to 12, in that the compound (C) is less likely to volatilize at the printing temperature and is more likely to volatilize at the sintering temperature.
[0027] The compound (C) represented by formula (I) is preferably not easily volatilized at printing temperatures, and has a boiling point (under normal pressure) of, for example, 160° C. or higher, preferably 190° C. or higher, more preferably 190 to 290° C., and even more preferably 200 to 260° C. If the boiling point is below the above range, the compound is likely to volatilize and the viscosity to vary when the bonding conductor paste is prepared or printed, and it tends to be difficult to form a conductive wiring or a bonding structure evenly and with high precision.
[0028] In addition, it is preferable that the compound (C) represented by formula (I) quickly volatilizes during sintering, and the square root of the cohesive energy density (SP value; (cal / cm 3 ) 1 / 2 ) is, for example, 11.0 or less, preferably 10.0 or less, and more preferably 9.0 or less. The SP value (at 25° C.) can be calculated by the Fedors formula.
[0029] In the compound (C) represented by formula (I), R a is a hydrocarbon group having 1 to 6 carbon atoms, and R b is a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, X is a propylene group, and n is 2, specific examples thereof include dipropylene glycol mono C ethers such as dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoisopropyl ether, dipropylene glycol monobutyl ether, dipropylene glycol monoisobutyl ether, dipropylene glycol monopentyl ether, and dipropylene glycol monoisopentyl ether. 1-6Alkyl ethers; dipropylene glycol dimethyl ether, dipropylene glycol methyl ethyl ether, dipropylene glycol methyl propyl ether, dipropylene glycol methyl butyl ether, dipropylene glycol methyl isobutyl ether, dipropylene glycol methyl pentyl ether, dipropylene glycol methyl isopentyl ether, dipropylene glycol diethyl ether, dipropylene glycol ethyl propyl ether, dipropylene glycol ethyl butyl ether, dipropylene glycol ethyl isobutyl ether, dipropylene glycol ethyl pentyl ether, dipropylene glycol ethyl isopentyl ether, dipropylene glycol dipropyl ether , dipropylene glycol propyl butyl ether, dipropylene glycol propyl isobutyl ether, dipropylene glycol propyl pentyl ether, dipropylene glycol propyl isopentyl ether, dipropylene glycol dibutyl ether, dipropylene glycol diisobutyl ether, dipropylene glycol butyl isobutyl ether, dipropylene glycol butyl pentyl ether, dipropylene glycol butyl isopentyl ether, dipropylene glycol isobutyl pentyl ether, dipropylene glycol isobutyl isopentyl ether, dipropylene glycol dipentyl ether, dipropylene glycol pentyl isopentyl ether, etc. 1-6 Mention may be made of alkyl ethers (including isomers).
[0030] In the compound (C) represented by formula (I), R a is a hydrocarbon group having 1 to 6 carbon atoms, and R bSpecific examples of the propylene glycol monoalkyl ether in the case where X is a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, X is a propylene group, and n is 3 include tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monoisopropyl ether, tripropylene glycol monobutyl ether, tripropylene glycol monoisobutyl ether, tripropylene glycol monopentyl ether, and tripropylene glycol monoisopentyl ether. 1-6 Alkyl ethers; tripropylene glycol dimethyl ether, tripropylene glycol methyl ethyl ether, tripropylene glycol methyl propyl ether, tripropylene glycol methyl butyl ether, tripropylene glycol methyl isobutyl ether, tripropylene glycol methyl pentyl ether, tripropylene glycol methyl isopentyl ether, tripropylene glycol diethyl ether, tripropylene glycol ethyl propyl ether, tripropylene glycol ethyl butyl ether, tripropylene glycol ethyl isobutyl ether, tripropylene glycol ethyl pentyl ether, tripropylene glycol ethyl isopentyl ether, tripropylene glycol dipropyl ether , tripropylene glycol propyl butyl ether, tripropylene glycol propyl isobutyl ether, tripropylene glycol propyl pentyl ether, tripropylene glycol propyl isopentyl ether, tripropylene glycol dibutyl ether, tripropylene glycol diisobutyl ether, tripropylene glycol butyl isobutyl ether, tripropylene glycol butyl pentyl ether, tripropylene glycol butyl isopentyl ether, tripropylene glycol isobutyl pentyl ether, tripropylene glycol isobutyl isopentyl ether, tripropylene glycol dipentyl ether, tripropylene glycol pentyl isopentyl ether, etc. 1-6 Mention may be made of alkyl ethers (including isomers).
[0031] In the compound (C) represented by formula (I), R a is a hydrocarbon group having 1 to 6 carbon atoms, and R b Specific examples of the case where X is a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, X is an ethylene group, and n is an integer of 1 to 3 include ethylene glycol mono-C ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, and ethylene glycol monohexyl ether. 1-6 Alkyl ethers; ethylene glycol di-C such as ethylene glycol methyl-n-propyl ether, ethylene glycol methyl-n-butyl ether, and ethylene glycol methyl isoamyl ether 1-6 Alkyl ethers; diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, and other diethylene glycol mono C 1-6 Alkyl ethers; diethylene glycol di-C such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, and diethylene glycol methyl-n-butyl ether 1-6 Alkyl ethers; triethylene glycol monomethyl ether, triethylene glycol monobutyl ether, and other triethylene glycol mono-C 1-6 Alkyl ethers; triethylene glycol di-C such as triethylene glycol methyl-n-butyl ether 1-10 Alkyl ethers and the like (including isomers).
[0032] In the compound (C) represented by formula (I), R a is an acyl group, and R bis a hydrogen atom or a monovalent group selected from a hydrocarbon group and an acyl group having 1 to 6 carbon atoms, X is an ethylene group or a propylene group, and n is an integer of 1 to 3. Specific examples of the compound in which n is an integer of 1 to 3 include C 1 -C 2 -C ...1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 -C 1 2-3 Alkylene glycol C 1-6 Alkyl Ether C 1-10 Alkyl esters; diethylene glycol n-butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate, etc. 2-3 Alkylene glycol C 1-6 Alkyl Ether C 1-10 Alkyl esters; triethylene glycol n-butyl ether acetate, triethylene glycol ethyl ether acetate, triethylene glycol butyl ether acetate, tripropylene glycol methyl ether acetate, etc. 2-3 Alkylene glycol C 1-6 Alkyl Ether C 1-10 Alkyl esters; propylene glycol diacetate, etc. 2-3 Alkylene glycol di-C 1-10 Alkyl esters and the like (including isomers).
[0033] In the compound (C) represented by formula (I), R a , R b Specific examples of compounds in which X and n are other than those mentioned above include compounds corresponding to the above examples. The above solvents can be used alone or in combination of two or more. It is preferable to appropriately select the type and content of the solvent from among these so as to meet the above conditions.
[0034] The bondable conductor paste of the present disclosure may contain one or more other solvents (e.g., ethyl acetate lactate, tetrahydrofurfuryl acetate, tetrahydrofurfuryl alcohol, ethylene glycol, etc.) in addition to the above, but the content of these solvents is, for example, preferably 30% by weight or less of the total amount of solvents contained in the bondable conductor paste of the present disclosure, more preferably 20% by weight or less, even more preferably 15% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, and even more preferably 1% by weight or less. If the content of other solvents exceeds the above range, clogging of the coating device tends to occur easily when a solvent with too high volatility is contained in a large amount, and if a solvent with too low volatility is contained in a large amount, quick-drying property is impaired, and a process such as heating is required to dry after application, which tends to reduce workability.
[0035] Therefore, the content of the compound (C) represented by the formula (I) in the total amount of the solvent is, for example, 70 to 100% by weight, and the lower limit is preferably 80% by weight, more preferably 85% by weight, even more preferably 90% by weight, even more preferably 95% by weight, and even more preferably 99% by weight.
[0036] The content of the compound (C) represented by the formula (I) is, for example, 1 to 50 parts by weight, preferably 2 to 30 parts by weight, and more preferably 3 to 30 parts by weight, relative to 100 parts by weight of the conductive particles (the total of the silver particles (A) and the silver particles (B)).
[0037] (Conductive particles) The bondable conductor paste of the present disclosure contains, as conductive particles, silver particles (A) having an average particle size of 1 nm or more and less than 100 nm, and silver particles (B) having an average particle size of 0.1 μm or more and 10 μm or less.
[0038] [Silver particles (A)] The silver particles (A) contained in the bondable conductor paste of the present disclosure are silver nanoparticles having an average particle size of 1 nm or more and less than 100 nm, and a configuration in which the surfaces are coated with a protective agent containing an amine, more specifically, a configuration in which unshared electron pairs of the amine are electrically coordinated on the surfaces of the silver particles (A). By having this configuration, the silver particles (A) in the present disclosure are prevented from re-agglomerating with each other, and can stably maintain a highly dispersed state in the bondable conductor paste.
[0039] The average particle size (median size) of the silver particles (A) is, as described above, 0.1 nm or more and less than 100 nm, preferably 0.5 to 90 nm, more preferably 1 to 80 nm, and even more preferably 1 to 75 nm. The particle size is determined as the average particle size (median size) converted into a volume distribution based on the particle size determined by observation with a transmission electron microscope (TEM) and assuming that the particles have an aspect ratio of 1.
[0040] The proportion of silver particles (A) in the total silver particles contained in the bondable conductor paste of the present disclosure is, for example, 50% by weight or less, preferably 45% by weight or less, and more preferably 40% by weight or less. When the silver particles (A) are contained in the above range, it is preferable in that the printability is improved and that the paste can be sintered quickly even in an inert gas atmosphere such as nitrogen to form a high bond strength between the substrate and the electronic element. On the other hand, the proportion of the silver particles (A) is, for example, 1% by weight or more, preferably 3% by weight or more, and more preferably 4% by weight or more.
[0041] The content of silver particles (A) is, for example, 1 to 45% by weight, preferably 2 to 43% by weight, and more preferably 3 to 40% by weight, of the total amount of the bonding conductor paste, from the viewpoints of obtaining a sintered body having good electrical conductivity, excellent dispersion stability (i.e., high dispersibility can be stably maintained over a long period of time and an increase in viscosity can be suppressed), improving printability, and enabling rapid sintering even in an inert gas atmosphere such as nitrogen to form a high bonding strength between a substrate and an electronic element.
[0042] [Method of producing silver particles (A)] The silver particles (A) are prepared by mixing an amine with a silver compound to generate a complex compound containing the silver compound and the amine, The silver particles (A) can be produced by heating the complex compound to thermally decompose it. Thus, the method for producing silver particles (A) mainly includes a step of producing a complex compound and a step of thermally decomposing the complex compound.
[0043] In the present disclosure, the silver compound is a silver compound that is easily decomposed by heating to generate metallic silver. As such a silver compound, silver carboxylate such as silver formate, silver acetate, silver oxalate, silver malonate, silver benzoate, and silver phthalate; silver halide such as silver fluoride, silver chloride, silver bromide, and silver iodide; silver sulfate, silver nitrate, and silver carbonate can be used, but silver oxalate is preferably used from the viewpoint that it easily generates metallic silver by decomposition and is unlikely to generate impurities other than silver. Silver oxalate has a high silver content, and is advantageous in that metallic silver can be obtained as it is by thermal decomposition without requiring a reducing agent, and impurities derived from the reducing agent are unlikely to remain.
[0044] In addition, in order to obtain a composite with silver, the above silver compound may be used in combination with a metal compound other than silver. The other metal compound is a metal compound that is easily decomposed by heating to generate the target metal. As the other metal compound, a metal salt corresponding to the above silver compound, for example, a metal carboxylate; a metal halide; a metal sulfate, a metal nitrate, a metal carbonate, or other metal salt compound, can be used. Among these, a metal oxalate is preferably used from the viewpoint that it easily generates a metal by decomposition and is unlikely to generate impurities other than the metal. Examples of the other metal include Al, Au, Pt, Pd, Cu, Co, Cr, In, and Ni. The silver composite is made of silver and one or more other metals, and examples thereof include Au-Ag, Ag-Cu, Au-Ag-Cu, and Au-Ag-Pd. Based on the total metal, silver accounts for at least 20% by weight, usually at least 50% by weight, for example at least 80% by weight.
[0045] In the present disclosure, in the step of producing a complex compound, the amine and the silver compound may be mixed without a solvent. However, it is preferable to mix them in the presence of an alcohol solvent having 3 or more carbon atoms to produce a complex compound containing the silver compound and the amine.
[0046] As the alcohol solvent, an alcohol having 3 to 10 carbon atoms, preferably an alcohol having 4 to 6 carbon atoms, can be used. Examples of the alcohol solvent include n-propanol (boiling point bp: 97°C), isopropanol (bp: 82°C), n-butanol (bp: 117°C), isobutanol (bp: 107.89°C), sec-butanol (bp: 99.5°C), tert-butanol (bp: 82.45°C), n-pentanol (bp: 136°C), n-hexanol (bp: 156°C), n-octanol (bp: 194°C), and 2-octanol (bp: 174°C). Among these, butanols and hexanols selected from n-butanol, isobutanol, sec-butanol, and tert-butanol are preferred in consideration of the ability to increase the temperature of the subsequent thermal decomposition step of the complex compound and the convenience of post-treatment after the formation of silver particles (A). In particular, n-butanol and n-hexanol are preferable.
[0047] In order to sufficiently stir the silver compound-alcohol slurry, the alcohol solvent is used in an amount of, for example, 120 parts by weight or more, preferably 130 parts by weight or more, and more preferably 150 parts by weight or more, relative to 100 parts by weight of the silver compound. The upper limit of the amount of the alcohol solvent is not particularly limited, and may be, for example, 1000 parts by weight or less, preferably 800 parts by weight or less, and more preferably 500 parts by weight or less, relative to 100 parts by weight of the silver compound.
[0048] In the present disclosure, mixing of the amine and the silver compound in the presence of an alcohol solvent having 3 or more carbon atoms can take several forms. For example, first, a solid silver compound and an alcohol solvent are mixed to obtain a silver compound-alcohol slurry [slurry formation step], and then an amine may be added to the obtained silver compound-alcohol slurry. The slurry refers to a mixture in which a solid silver compound is dispersed in an alcohol solvent. The solid silver compound may be charged into a reaction vessel, and the alcohol solvent may be added thereto to obtain a slurry. Alternatively, the amine and alcohol solvent may be charged to a reaction vessel and the silver compound-alcohol slurry added thereto.
[0049] In the present disclosure, as the amine functioning as a complexing agent and / or a protecting agent, for example, at least one of aliphatic hydrocarbon monoamine (1) having a total number of carbon atoms in the hydrocarbon group of 6 or more, aliphatic hydrocarbon monoamine (2) consisting of an aliphatic hydrocarbon group and one amino group, the total number of carbon atoms in the aliphatic hydrocarbon group being 5 or less, and aliphatic hydrocarbon diamine (3) consisting of an aliphatic hydrocarbon group and two amino groups, the total number of carbon atoms in the aliphatic hydrocarbon group being 8 or less may be used. These components are usually used as an amine mixture, but the mixing of the amine with the silver compound (or its alcohol slurry) does not necessarily need to be performed using the amines in a mixed state. The amines may be added sequentially to the silver compound (or its alcohol slurry).
[0050] In this specification, the term "aliphatic hydrocarbon monoamine" is an established term, and refers to a compound consisting of one to three monovalent aliphatic hydrocarbon groups and one amino group. The "hydrocarbon group" refers to a group consisting of only carbon and hydrogen. However, the aliphatic hydrocarbon monoamine (1) and the aliphatic hydrocarbon monoamine (2) may have a substituent containing a heteroatom (atom other than carbon and hydrogen) such as an oxygen atom or a nitrogen atom in the hydrocarbon group, as necessary. This nitrogen atom does not constitute an amino group.
[0051] Moreover, the term "aliphatic hydrocarbon diamine" refers to a compound consisting of a divalent aliphatic hydrocarbon group (alkylene group), two amino groups interposed between the aliphatic hydrocarbon group, and, in some cases, an aliphatic hydrocarbon group (alkyl group) that replaces the hydrogen atom of the amino group. However, the aliphatic hydrocarbon diamine (3) may have a substituent containing a heteroatom (atom other than carbon and hydrogen) such as an oxygen atom or a nitrogen atom in the hydrocarbon group as necessary. The nitrogen atom does not constitute an amino group.
[0052] Aliphatic hydrocarbon monoamines (1) having a total of 6 or more carbon atoms have a high function as protective agents (stabilizers) for the surfaces of the resulting silver particles due to their hydrocarbon chains.
[0053] The aliphatic hydrocarbon monoamine (1) includes primary amines, secondary amines, and tertiary amines. Examples of primary amines include saturated aliphatic hydrocarbon monoamines (i.e., alkyl monoamines) having a straight-chain aliphatic hydrocarbon group having 6 to 18 carbon atoms, such as hexylamine, heptylamine, octylamine, nonylamine, decylamine, undecylamine, dodecylamine, tridecylamine, tetradecylamine, pentadecylamine, hexadecylamine, heptadecylamine, and octadecylamine. Examples of saturated aliphatic hydrocarbon monoamines include branched aliphatic hydrocarbon monoamines having a branched aliphatic hydrocarbon group having 6 to 16 carbon atoms, preferably 6 to 8 carbon atoms, such as isohexylamine, 2-ethylhexylamine, and tert-octylamine, in addition to the above-mentioned straight-chain aliphatic monoamines. Cyclohexylamine is also included. Furthermore, unsaturated aliphatic hydrocarbon monoamines (i.e., alkenyl monoamines) such as oleylamine are included.
[0054] Examples of secondary amines include linear dialkyl monoamines such as N,N-dipropylamine, N,N-dibutylamine, N,N-dipentylamine, N,N-dihexylamine, N,N-dipeptylamine, N,N-dioctylamine, N,N-dinonylamine, N,N-didecylamine, N,N-diundecylamine, N,N-didodecylamine, and N-propyl-N-butylamine. Examples of tertiary amines include tributylamine and trihexylamine.
[0055] In addition, examples of branched amines include secondary amines such as N,N-diisohexylamine and N,N-di(2-ethylhexyl)amine. In addition, examples of tertiary amines include triisohexylamine and tri(2-ethylhexyl)amine. In the case of N,N-di(2-ethylhexyl)amine, the number of carbon atoms in the 2-ethylhexyl group is 8, but the total number of carbon atoms contained in the amine compound is 16. In the case of tri(2-ethylhexyl)amine, the total number of carbon atoms contained in the amine compound is 24.
[0056] Among the monoamines (1), in the case of linear monoamines, saturated aliphatic hydrocarbon monoamines having 6 or more carbon atoms are preferred. By making the number of carbon atoms 6 or more, when the amino group is adsorbed on the surface of the silver particles, a distance between the silver particles and other silver particles can be secured, improving the effect of preventing aggregation between the silver particles. There is no particular upper limit on the number of carbon atoms, but in consideration of ease of availability, ease of removal during firing, and the like, saturated aliphatic monoamines having up to 18 carbon atoms are usually preferred. In particular, alkyl monoamines having 6 to 12 carbon atoms, such as hexylamine, heptylamine, octylamine, nonylamine, decylamine, undecylamine, and dodecylamine, are preferably used. Of the linear aliphatic hydrocarbon monoamines, only one may be used, or two or more may be used in combination.
[0057] Furthermore, when a branched aliphatic hydrocarbon monoamine compound is used, a larger area of the silver particle surface can be covered with a smaller amount of the compound attached to the silver particle surface due to the steric factor of the branched aliphatic hydrocarbon group, compared to when a straight-chain aliphatic hydrocarbon monoamine compound with the same number of carbon atoms is used. Therefore, the silver particles (A) can be appropriately stabilized with a smaller amount of the compound attached to the silver particle surface. Since the amount of protective agent (organic stabilizer) to be removed during firing is small, the organic stabilizer can be efficiently removed even when firing at a low temperature of 200°C or less, and the sintering of the silver particles proceeds sufficiently.
[0058] Among the above branched aliphatic hydrocarbon monoamines, branched alkyl monoamine compounds having 5 to 6 carbon atoms in the main chain, such as isohexylamine and 2-ethylhexylamine, are preferred. When the main chain has 5 to 6 carbon atoms, it is easy to obtain an appropriate stabilization of the silver particles (A). From the viewpoint of the steric factor of the branched aliphatic group, it is effective that the branch is formed at the second carbon atom from the N atom side, as in 2-ethylhexylamine. As the branched aliphatic monoamine, only one type may be used, or two or more types may be used in combination.
[0059] In the present disclosure, as the aliphatic hydrocarbon monoamine (1), the linear aliphatic hydrocarbon monoamine and the branched aliphatic hydrocarbon monoamine may be used in combination to obtain the respective advantages.
[0060] Aliphatic hydrocarbon monoamines (2) having a total carbon number of 5 or less have a shorter carbon chain length than aliphatic monoamines (1) having a total carbon number of 6 or more, and therefore are considered to have a low function as a protective agent (stabilizer) in themselves, but are more polar than the aliphatic monoamines (1) and have a high coordination ability to silver in silver compounds, and are therefore considered to be effective in promoting complex formation. In addition, because the carbon chain length is short, they can be removed from the silver particle surface in a short time of 30 minutes or less or 20 minutes or less, even in low-temperature calcination at, for example, 120°C or less or about 100°C or less, and are therefore effective in low-temperature calcination of the obtained silver particles (A).
[0061] Examples of the aliphatic hydrocarbon monoamine (2) include saturated aliphatic hydrocarbon monoamines having 2 to 5 carbon atoms (i.e., alkyl monoamines), such as ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, pentylamine, isopentylamine, tert-pentylamine, etc. Also included are dialkyl monoamines, such as N,N-dimethylamine, N,N-diethylamine, N-methyl-N-propylamine, and N-ethyl-N-propylamine.
[0062] Among these, n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, pentylamine, isopentylamine, tert-pentylamine, etc. are preferred, and the above-mentioned butylamines are more preferred. Among the aliphatic hydrocarbon monoamines (2), only one may be used, or two or more may be used in combination.
[0063] Aliphatic hydrocarbon diamines (3) having a total carbon number of 8 or less have a high coordination ability to silver of silver compounds, and are effective in promoting the formation of complexes. Aliphatic hydrocarbon diamines generally have a higher polarity than aliphatic hydrocarbon monoamines, and have a higher coordination ability to silver of silver compounds. In addition, the aliphatic hydrocarbon diamines (3) have the effect of promoting thermal decomposition at a lower temperature and in a shorter time in the thermal decomposition step of a complex compound, and can produce silver nanoparticles more efficiently. Furthermore, since the protective coating of silver particles containing the aliphatic diamines (3) has a high polarity, the dispersion stability of silver particles in a dispersion medium containing a highly polar solvent is improved. Furthermore, since the aliphatic diamines (3) have a short carbon chain length, they can be removed from the surface of silver particles in a short time of 30 minutes or less, or 20 minutes or less, even in low-temperature firing at 120°C or less, or about 100°C or less, and are therefore effective in low-temperature and short-time firing of the obtained silver particles (A).
[0064] The aliphatic hydrocarbon diamine (3) is not particularly limited, but examples thereof include ethylenediamine, N,N-dimethylethylenediamine, N,N'-dimethylethylenediamine, N,N-diethylethylenediamine, N,N'-diethylethylenediamine, 1,3-propanediamine, 2,2-dimethyl-1,3-propanediamine, N,N-dimethyl-1,3-propanediamine, N,N'-dimethyl-1,3-propanediamine, N,N-diethyl-1,3-propanediamine, N,N'-diethyl-1,3-propanediamine, and N,N'-diethyl-1,3-propanediamine. Examples of such diamines include pananediamine, 1,4-butanediamine, N,N-dimethyl-1,4-butanediamine, N,N'-dimethyl-1,4-butanediamine, N,N-diethyl-1,4-butanediamine, N,N'-diethyl-1,4-butanediamine, 1,5-pentanediamine, 1,5-diamino-2-methylpentane, 1,6-hexanediamine, N,N-dimethyl-1,6-hexanediamine, N,N'-dimethyl-1,6-hexanediamine, 1,7-heptanediamine, and 1,8-octanediamine. All of these are alkylenediamines having a total of 8 carbon atoms or less, in which at least one of the two amino groups is a primary amino group or a secondary amino group, and have a high coordination ability with silver compounds and are effective in promoting complex formation.
[0065] Among these, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dimethyl-1,3-propanediamine, N,N-diethyl-1,3-propanediamine, N,N-dimethyl-1,4-butanediamine, N,N-diethyl-1,4-butanediamine, and N,N-dimethyl-1,6-hexanediamine have two amino groups, one of which is a primary amino group (-NH 2 ), and the other is a tertiary amino group (-NR 1 R 2 ) is preferably an alkylenediamine having a total of 8 or less carbon atoms. A preferred alkylenediamine is represented by the following structural formula:
[0066] R 1 R 2 NR-NH 2 Here, R represents a divalent alkylene group, R1 and R 2 may be the same or different and represent an alkyl group, provided that R, R 1 and R 2 The total number of carbon atoms is 8 or less. The alkylene group usually does not contain a heteroatom (atom other than carbon and hydrogen) such as an oxygen atom or a nitrogen atom, but may have a substituent containing the heteroatom as necessary. The alkyl group usually does not contain a heteroatom such as an oxygen atom or a nitrogen atom, but may have a substituent containing the heteroatom as necessary.
[0067] When one of the two amino groups is a primary amino group, the silver compound has a high coordination ability with silver, which is advantageous for complex formation, and when the other is a tertiary amino group, the tertiary amino group has poor coordination ability with silver atoms, so that the complex formed is prevented from having a complex network structure. If the complex has a complex network structure, a high temperature may be required for the thermal decomposition process of the complex. Furthermore, among these, diamines having a total carbon number of 6 or less are preferred, and diamines having a total carbon number of 5 or less are more preferred, from the viewpoint that they can be removed from the silver particle surface in a short time even in low-temperature firing. Of the aliphatic hydrocarbon diamines (3), only one type may be used, or two or more types may be used in combination.
[0068] In the present disclosure, the proportions of the aliphatic hydrocarbon monoamine (1) having a total carbon number of 6 or more and either or both of the aliphatic hydrocarbon monoamine (2) having a total carbon number of 5 or less and the aliphatic hydrocarbon diamine (3) having a total carbon number of 8 or less are not particularly limited. For example, based on the total amines [(1)+(2)+(3)], The aliphatic monoamine (1): 5 mol% to 65 mol% Total amount of the aliphatic monoamine (2) and the aliphatic diamine (3): 35 mol % to 95 mol % It is preferable to set the content of the aliphatic monoamine (1) to 5 mol % to 65 mol %, so that the carbon chain of the component (1) can easily provide a protective and stabilizing function for the surface of the resulting silver particles. If the content of the component (1) is less than 5 mol %, the protective and stabilizing function may not be fully exerted. On the other hand, if the content of the component (1) exceeds 65 mol %, the protective and stabilizing function is sufficient, but the component (1) is difficult to remove by low-temperature firing. When the branched aliphatic monoamine is used as the component (1), it is preferable to set the content of the branched aliphatic monoamine to 10 mol % to 50 mol % so as to satisfy the aliphatic monoamine (1): 5 mol % to 65 mol %.
[0069] When the aliphatic monoamine (1) and further both the aliphatic monoamine (2) and the aliphatic diamine (3) are used, the ratio of their use is not particularly limited, but may be, for example, based on the total amines [(1)+(2)+(3)], The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic monoamine (2): 5 mol% to 70 mol% The aliphatic diamine (3): 5 mol% to 50 mol% When the branched aliphatic monoamine is used as the component (1), the branched aliphatic monoamine is preferably 10 mol % to 50 mol % so as to satisfy the aliphatic monoamine (1): 5 mol % to 65 mol %.
[0070] In this case, the lower limit of the content of the component (1) is preferably 10 mol % or more, more preferably 20 mol % or more, and the upper limit of the content of the component (1) is preferably 65 mol % or less, more preferably 60 mol % or less.
[0071] By setting the content of the aliphatic monoamine (2) to 5 mol % to 70 mol %, the complex formation promoting effect is easily obtained, and the component (2) itself can contribute to low-temperature and short-time firing, and further, the action of assisting the removal of the aliphatic diamine (3) from the silver particle surface during firing is easily obtained. If the content of the component (2) is less than 5 mol %, the complex formation promoting effect may be weak, or the component (3) may be difficult to remove from the silver particle surface during firing. On the other hand, if the content of the component (2) exceeds 70 mol %, the complex formation promoting effect is obtained, but the content of the aliphatic monoamine (1) is relatively small, and it is difficult to protect and stabilize the surface of the silver particles formed. The lower limit of the content of the component (2) is preferably 10 mol % or more, and more preferably 15 mol % or more. The upper limit of the content of the component (2) is preferably 65 mol % or less, and more preferably 60 mol % or less.
[0072] By setting the content of the aliphatic diamine (3) to 5 mol % or more, the complex formation promoting effect and the thermal decomposition promoting effect of the complex are easily obtained, and since the protective coating of the silver particles containing the aliphatic diamine (3) has high polarity, the dispersion stability of the silver particles in a dispersion medium containing a highly polar solvent is improved. When the content of the (3) component is less than 5 mol %, the complex formation promoting effect and the thermal decomposition promoting effect of the complex may be weak. On the other hand, when the content of the (3) component is more than 50 mol %, the complex formation promoting effect and the thermal decomposition promoting effect of the complex are obtained, but the content of the aliphatic monoamine (1) is relatively small, and it is difficult to obtain protection and stabilization of the surface of the generated silver particles. The lower limit of the content of the (3) component is preferably 5 mol % or more, and more preferably 10 mol % or more. The upper limit of the content of the (3) component is preferably 45 mol % or less, and more preferably 40 mol % or less.
[0073] When the aliphatic monoamine (1) and the aliphatic monoamine (2) are used (without using the aliphatic diamine (3)), their use ratio is not particularly limited, but taking into consideration the action of each component, the ratio may be, for example, based on the total amines [(1)+(2)], as follows: The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic monoamine (2): 35 mol% to 95 mol% When the branched aliphatic monoamine is used as the component (1), the branched aliphatic monoamine is preferably 10 mol % to 50 mol % so as to satisfy the aliphatic monoamine (1): 5 mol % to 65 mol %.
[0074] When the aliphatic monoamine (1) and the aliphatic diamine (3) are used (without using the aliphatic monoamine (2)), their use ratio is not particularly limited. Taking into consideration the action of each component, the ratio based on the total amines [(1)+(3)] can be, for example, The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic diamine (3): 35 mol% to 95 mol% When the branched aliphatic monoamine is used as the component (1), the branched aliphatic monoamine is preferably 10 mol % to 50 mol % so as to satisfy the aliphatic monoamine (1): 5 mol % to 65 mol %.
[0075] The above-mentioned proportions of the aliphatic monoamine (1), the aliphatic monoamine (2) and / or the aliphatic diamine (3) are all examples and may be changed in various ways.
[0076] In the present disclosure, when the aliphatic monoamine (2) and / or the aliphatic diamine (3), which have a high coordination ability to silver of a silver compound, are used, the amount of the aliphatic monoamine (1) having a total carbon number of 6 or more adhered to the silver particle surface can be reduced depending on the ratio of their use. Therefore, even in the case of firing at a low temperature for a short time, these aliphatic amine compounds are easily removed from the silver particle surface, and sintering of the silver particles (A) proceeds sufficiently.
[0077] In the present disclosure, the total amount of the aliphatic hydrocarbyl amines [e.g., (1), (2) and / or (3)] is not particularly limited, but may be about 1 to 50 moles per mole of silver atoms of the raw silver compound. If the total amount of the amine components [(1), (2) and / or (3)] is less than 1 mole per mole of silver atoms, there is a possibility that silver compounds that are not converted to complex compounds will remain in the complex compound production process, and in the subsequent thermal decomposition process, the uniformity of silver particles will be impaired, causing particle enlargement, or silver compounds will remain without thermal decomposition. On the other hand, there is thought to be little benefit if the total amount of the amine components [(1), (2) and / or (3)] exceeds about 50 moles per mole of the silver atoms. In order to prepare a dispersion of silver nanoparticles substantially in a solvent-free environment, the total amount of the amine components may be, for example, about 2 moles or more. By setting the total amount of the amine components to about 2 to 50 moles, the complex compound production process and the thermal decomposition process can be carried out smoothly. The lower limit of the total amount of the amine components is preferably 2 moles or more, and more preferably 6 moles or more, per mole of silver atoms of the silver compound. Note that a silver oxalate molecule contains two silver atoms.
[0078] In the present disclosure, in order to further improve the dispersibility of the silver particles (A) in the dispersion medium, an aliphatic carboxylic acid (4) may be further used as a stabilizer. The aliphatic carboxylic acid (4) may be used together with the amines, and may be used by being contained in the amine mixture. By using the aliphatic carboxylic acid (4), the stability of the silver nanoparticles, particularly the stability in a paint state in which the silver nanoparticles are dispersed in an organic solvent, may be improved.
[0079] As the aliphatic carboxylic acid (4), a saturated or unsaturated aliphatic carboxylic acid is used. Examples of the saturated aliphatic monocarboxylic acid include butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, nonadecanoic acid, icosanoic acid, and eicosenoic acid, and the like, and the unsaturated aliphatic monocarboxylic acid includes 8 or more carbon atoms, such as oleic acid, elaidic acid, linoleic acid, and palmitoleic acid.
[0080] Among these, saturated or unsaturated aliphatic monocarboxylic acids having 8 to 18 carbon atoms are preferred. By making the number of carbon atoms 8 or more, when the carboxylic acid group is adsorbed on the surface of the silver particle, a distance between the silver particles and other silver particles can be secured, improving the effect of preventing aggregation between the silver particles. In consideration of ease of availability, ease of removal during firing, and the like, saturated or unsaturated aliphatic monocarboxylic acid compounds having up to 18 carbon atoms are usually preferred. In particular, octanoic acid, oleic acid, and the like are preferably used. Of the aliphatic carboxylic acids (4), only one type may be used, or two or more types may be used in combination.
[0081] When the aliphatic carboxylic acid (4) is used, it is preferably used in an amount of, for example, about 0.05 to 10 moles, preferably 0.1 to 5 moles, more preferably 0.5 to 2 moles, per mole of silver atoms in the raw silver compound. If the amount of the component (4) is less than 0.05 moles per mole of silver atoms, the effect of improving the stability in the dispersed state by adding the component (4) is weak. On the other hand, if the amount of the component (4) reaches 10 moles, the effect of improving the stability in the dispersed state is saturated, and the component (4) becomes difficult to remove by low-temperature firing. However, in consideration of the removal of the component (4) by low-temperature firing, the aliphatic carboxylic acid (4) may not be used.
[0082] In the present disclosure, a mixed solution containing each of the aliphatic hydrocarbon amine components to be used is usually prepared; for example, an amine mixed solution containing the aliphatic monoamine (1) and either or both of the aliphatic monoamine (2) and the aliphatic diamine (3) is prepared [amine mixed solution preparation step].
[0083] The amine mixture can be prepared by stirring the amine (1), (2) and / or (3) components and, when used, the carboxylic acid (4) component in a predetermined ratio at room temperature.
[0084] An aliphatic hydrocarbon amine mixture containing each amine component is added to the silver compound (or its alcohol slurry) to generate a complex compound containing the silver compound and the amine [complex compound generation step]. Each amine component may be added successively to the silver compound (or its alcohol slurry) without forming a mixture.
[0085] A silver compound (or its alcohol slurry) is mixed with a predetermined amount of an amine mixture. The mixing is preferably performed at room temperature. "Room temperature" refers to 5 to 40°C depending on the ambient temperature. For example, 5 to 35°C (JIS Z 8703), 10 to 35°C, or 20 to 30°C. It may be normal room temperature (for example, in the range of 15 to 30°C). The mixing may be performed with stirring, or, since the coordination reaction of amines to the silver compound is accompanied by heat, it may be performed while appropriately cooling to the above temperature range, for example, about 5 to 15°C, and stirring. If the silver compound and the amine mixture are mixed in the presence of an alcohol having 3 or more carbon atoms, stirring and cooling can be performed well. The excess of the alcohol and amines play the role of a reaction medium.
[0086] In the conventional thermal decomposition method of silver amine complex, a liquid aliphatic amine component is first charged in a reaction vessel, and then a powdered silver compound (silver oxalate) is added thereto. The liquid aliphatic amine component is a flammable substance, and adding a powdered silver compound thereto is dangerous. That is, there is a risk of ignition due to static electricity caused by adding the powdered silver compound. In addition, there is a risk that the addition of the powdered silver compound will cause a complex formation reaction to proceed locally, resulting in an explosive exothermic reaction. If the silver compound and the amine mixture are mixed in the presence of the alcohol, such danger can be avoided. Therefore, it is safe even in scaled-up industrial production.
[0087] Since the complex compound formed generally exhibits a color according to its constituent components, the end point of the reaction of forming the complex compound can be detected by detecting the end of the color change of the reaction mixture by an appropriate spectroscopy method or the like. In addition, the complex compound formed by silver oxalate is generally colorless (visually observed as white), but even in such a case, the state of formation of the complex compound can be detected based on the morphological change such as the change in viscosity of the reaction mixture. For example, the time of the reaction of forming the complex compound is about 30 minutes to 3 hours. In this way, a silver-amine complex is obtained in a medium mainly composed of alcohol and amines.
[0088] Next, the obtained complex compound is heated and thermally decomposed to form silver particles (A) [complex compound thermal decomposition step]. Silver particles (A) are formed without using a reducing agent. However, if necessary, an appropriate reducing agent may be used within a range that does not impair the effects of the present disclosure.
[0089] In such a metal amine complex decomposition method, amines generally play a role in controlling the manner in which atomic metals generated by the decomposition of a metal compound aggregate to form fine particles, and in preventing re-aggregation between the fine particles by forming a coating on the surface of the formed fine metal particles. That is, it is considered that by heating a complex compound of a metal compound and an amine, the metal compound is thermally decomposed while maintaining the coordinate bond of the amine to the metal atom to generate atomic metal, and then the metal atoms coordinated with the amine aggregate to form metal nanoparticles covered with an amine protective film.
[0090] The thermal decomposition is preferably carried out while stirring the complex compound in a reaction medium mainly composed of alcohol (if used) and amines. The thermal decomposition may be carried out within a temperature range in which coated silver nanoparticles are produced, but from the viewpoint of preventing the amine from being removed from the silver particle surface, it is preferable to carry out the thermal decomposition at a temperature as low as possible within the above temperature range. In the case of a silver oxalate complex compound, the temperature can be, for example, about 80°C to 120°C, preferably about 95°C to 115°C, more specifically about 100°C to 110°C. In the case of a silver oxalate complex compound, decomposition occurs by heating at about 100°C, and silver ions are reduced, and coated silver nanoparticles can be obtained. In addition, while the thermal decomposition of silver oxalate itself generally occurs at about 200°C, the reason why the thermal decomposition temperature is reduced by about 100°C by forming a silver oxalate-amine complex compound is not clear, but it is presumed that this is because the coordination polymer structure formed by pure silver oxalate is cut when a complex compound of silver oxalate and amine is produced.
[0091] The thermal decomposition of the complex compound is preferably carried out in an atmosphere of an inert gas such as argon, but it can also be carried out in air.
[0092] The thermal decomposition of the complex compound results in a suspension with a blue luster. From this suspension, the excess amine and the like can be removed, for example, by settling the silver nanoparticles and performing decantation and washing with an appropriate solvent (water or organic solvent), to obtain the desired stable silver particles (A) [post-treatment process of silver nanoparticles]. After washing, the silver particles are dried to obtain the desired stable silver particle (A) powder. However, wet silver nanoparticles (N) may also be used to prepare a bonding conductor paste.
[0093] Water or an organic solvent is used for the decantation and washing operation. Examples of the organic solvent include aliphatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane, and tetradecane; alicyclic hydrocarbon solvents such as cyclohexane; aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene; alcohol solvents such as methanol, ethanol, propanol, and butanol; acetonitrile; and mixtures of these solvents.
[0094] In order to avoid the inclusion of solvents other than the compound (C) represented by the formula (I) in the bondable conductor paste of the present disclosure, the compound (C) represented by the formula (I) may be used as an organic solvent for the decantation and washing operation. In addition, after performing the decantation and washing operation using an organic solvent other than the compound (C) represented by the formula (I), the decantation and washing operation may be performed using the compound (C) represented by the formula (I). In that case, in order to avoid the inclusion of organic solvents other than the compound (C) represented by the formula (I), it is preferable to perform the decantation and washing operation multiple times (preferably 2 to 4 times) using the compound (C) represented by the formula (I).
[0095] In the silver nanoparticle formation process of the present disclosure, a reducing agent is not required, so there are no by-products derived from the reducing agent, the silver particles (A) can be easily separated from the reaction system, and high-purity silver particles (A) can be obtained. However, if necessary, an appropriate reducing agent may be used within a range that does not impair the effects of the present disclosure.
[0096] In this way, silver particles (A) are formed whose surfaces are coated with the protective agent used. The protective agent contains, for example, the aliphatic monoamine (1), and further contains either one or both of the aliphatic monoamine (2) and the aliphatic diamine (3), and further contains the carboxylic acid (4) when used. The content ratio of the protective agent is the same as the use ratio of the amine mixture. The same applies to the silver particles (A).
[0097] As the silver particles (A), commercially available products may be used, for example, low viscosity type (silver concentration 30 to 50% by mass) of silver nanoink "Picosil (registered trademark)" manufactured by Daicel Corporation.
[0098] [Silver particles (B)] As described above, the average particle size (median size) of the silver particles (B) is 0.1 to 10 μm, preferably 0.1 to 9 μm, and more preferably 0.3 to 8 μm. The average particle size (median size) of the silver particles (B) can be measured by a laser diffraction / scattering method.
[0099] The specific surface area of the silver particles (B) is, for example, 0.5 to 4.0 m 2 / g, preferably 0.6 to 3.0 m 2 / g, more preferably 0.7 to 2.5 m 2 / g, more preferably 0.8 to 2.5 m 2 The specific surface area of the silver particles (B) can be measured by the BET method.
[0100] The proportion of silver particles (B) in the total silver particles contained in the bonding conductor paste of the present disclosure is, for example, 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more. When the silver particles (B) are contained in the above range, it is preferable in that the silver particles (B) can be sintered quickly even in an inert gas atmosphere such as nitrogen, and a high bonding strength can be formed between the substrate and the electronic element. On the other hand, the proportion of the silver particles (B) is, for example, 99% by weight or less, preferably 97% by weight or less, and more preferably 95% by weight or less.
[0101] Among the silver particles (B), it is preferable to use a combination of silver particles (group) having different average particle sizes, since this allows the formation of conductor wiring or junction structures with even lower electrical resistance and excellent electrical properties. It is preferable to use a combination of silver particles (group) having an average particle size of 0.1 to 1.5 μm (more preferably 0.1 to 0.6 μm) and silver particles (group) having an average particle size of more than 1.5 μm and 8 μm or less (more preferably 5 to 8 μm) in a ratio of, for example, 70 / 30 to 30 / 70, preferably 40 / 60 to 60 / 40, more preferably 45 / 55 to 55 / 45 (former / latter: weight ratio).
[0102] The content of silver particles (B) is, for example, 20 to 95% by weight, preferably 30 to 90% by weight, and more preferably 40 to 90% by weight of the total amount of the bonding conductor paste, from the viewpoints of obtaining a sintered body having good electrical conductivity, excellent dispersion stability (i.e., high dispersibility can be stably maintained over a long period of time and an increase in viscosity can be suppressed), and the paste can be quickly sintered even in an inert gas atmosphere such as nitrogen to form a high bonding strength between the substrate and the electronic element.
[0103] The shape of the silver particles (B) can be, for example, spherical, flat, polyhedral, etc., and conductive particles of different shapes may be used in combination, or only conductive particles of the same shape may be used.
[0104] As the silver particles (B), commercially available products may be used, such as those available under the trade name "AgC-239" (average particle size (median size) 6.0 μm, manufactured by Fukuda Metal Foil & Powder Co., Ltd.) and those available under the trade name "S211A-10" (average particle size (median size) 0.54 μm, manufactured by Daiken Chemical Co., Ltd.).
[0105] The bondable conductor paste of the present disclosure may contain conductive particles other than silver particles (A) and silver particles (B) (hereinafter, sometimes referred to as "other conductive particles"). The content of the silver particles is, for example, 75% by weight or more, preferably 80% by weight or more, more preferably 85% by weight or more, and even more preferably 90% by weight or more of the total amount of conductive particles contained in the bondable conductor paste of the present disclosure. The upper limit of the content of silver particles is 100% by weight. Therefore, the content of the other conductive particles is, for example, 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, even more preferably 10% by weight or less, and even more preferably 5% by weight or less of the total amount of conductive particles contained in the bondable conductor paste of the present disclosure. When the silver particles are contained in the above range, it is preferable in that a conductor wiring or a bonded structure having particularly excellent electrical properties can be formed.
[0106] When other conductive particles are contained, the weight ratio of the silver particles to the other conductive particles (former:latter) contained in the bonding conductor paste of the present disclosure is, for example, 4:1 to 30:1, preferably 6:1 to 25:1, and more preferably 8:1 to 20:1.
[0107] Examples of the other conductive particles include palladium, platinum, gold, copper, nickel, etc. These may be used alone or in combination of two or more.
[0108] (Conductive adhesive paste) The bondable conductor paste of the present disclosure contains silver particles (A) and silver particles (B) as conductive particles, and a compound represented by formula (I) as a solvent.
[0109] The content of the solvent in the total amount (100 wt%) of the bonding conductor paste of the present disclosure (total content when two or more types are contained) is, for example, 1 to 50 wt%, preferably 2 to 40 wt%, and more preferably 3 to 30 wt%.
[0110] The content of the compound (C) represented by formula (I) in the total amount (100% by weight) of the bonding conductor paste of the present disclosure (the total content when two or more types are contained) is, for example, 1 to 50% by weight, preferably 2 to 40% by weight, and more preferably 3 to 30% by weight.
[0111] Furthermore, the content of conductive particles in the total amount (100% by weight) of the bonding conductor paste of the present disclosure (total content when two or more types are contained) is, for example, 50 to 99% by weight, preferably 60 to 97% by weight, and more preferably 70 to 95% by weight.
[0112] Furthermore, the content of silver particles (the total content of silver particles (A) and (B)) in the total amount (100% by weight) of the bonding conductor paste of the present disclosure is, for example, 50 to 99.8% by weight, preferably 60 to 97% by weight, and more preferably 70 to 95% by weight.
[0113] In the total amount (100 wt%) of the bonding conductor paste of the present disclosure, the total content of the compound (C) represented by formula (I) and the silver particles is, for example, 70 wt% or more, preferably 80 wt% or more, and more preferably 90 wt% or more. Therefore, the content of components other than the compound (C) represented by formula (I) and the silver particles contained in the bonding conductor paste of the present disclosure (the total content when two or more kinds are contained) is, for example, 30 wt% or less, preferably 20 wt% or less, and more preferably 10 wt% or less.
[0114] Furthermore, the content of organic components in the total amount (100 wt%) of the bonding conductor paste of the present disclosure is, for example, 15 wt% or less, preferably 13 wt% or less. The organic components include the compound (C) represented by formula (I) and may further include other solvents and organic additives (adhesives, thickeners, binders, etc.).
[0115] The bondable conductor paste of the present disclosure contains silver particles (A) and silver particles (B), and therefore can be rapidly sintered even in an inert gas atmosphere such as nitrogen, to form high-precision conductor wiring or bonded structures that can connect a substrate and an electronic element with high bonding strength.
[0116] The compound represented by formula (I) contained in the bonding conductor paste of the present disclosure has a slow volatilization rate at the printing temperature and a fast volatilization rate at the sintering temperature. Therefore, by using the bonding conductor paste of the present disclosure, it is possible to suppress the fluctuation of viscosity during printing and print evenly. During sintering, a sintered body with excellent bonding strength can be formed even at a low temperature (e.g., 150°C or higher and lower than 300°C, preferably 170 to 280°C) in an inert gas atmosphere such as nitrogen (sintering time is, for example, 0.1 to 2 hours, preferably 0.5 to 1.5 hours), and deterioration or damage of the substrate during the sintering process can be prevented.
[0117] The bonding conductor paste of the present disclosure can be applied to a substrate by a printing method (specifically, a dispenser printing method, a mask printing method, a screen printing method, an inkjet printing method, etc.), and then sintered to form a conductor wiring or a bonding structure.
[0118] The sintering temperature is, for example, not less than 150° C. and less than 300° C., preferably 160 to 280° C. The sintering time is, for example, 0.1 to 2 hours, preferably 0.5 to 1.5 hours.
[0119] The sintering is preferably carried out in an inert gas atmosphere such as a nitrogen atmosphere or an argon atmosphere, since this can prevent oxidation of unprotected copper and nickel substrates and wiring in the semiconductor module due to oxygen in the air.
[0120] The thickness of the bonding conductor paste of the present disclosure applied onto the substrate is in the range of, for example, 15 to 400 μm, preferably 20 to 250 μm, and more preferably 40 to 180 μm, such that the thickness of the conductor wiring or bonded structure formed by the above method is, for example, 15 to 400 μm, preferably 20 to 250 μm, and more preferably 40 to 180 μm.
[0121] Examples of substrates on which conductor wiring or bonded structures are formed include ceramic substrates, SiC substrates, gallium nitride substrates, metal substrates, glass epoxy substrates, BT resin substrates, glass substrates, resin substrates, etc. Since the bondable conductor paste of the present disclosure can be sintered at low temperatures as described above, substrates that are sensitive to heat can also be used.
[0122] The shape of the conductor wiring and the junction structure is not particularly limited as long as it is a shape that allows connection of electronic elements.
[0123] The bonding conductor paste of the present disclosure may contain an adhesive (e.g., a polymeric compound having a molecular weight of 10,000 or more, such as an epoxy resin, a silicone resin, or an acrylic resin), but the content thereof is, for example, 10% by weight or less of the total amount (100 weight) of the bonding conductor paste, preferably 5% by weight or less, more preferably 1% by weight or less, and even more preferably 0.5% by weight or less. Therefore, according to the bonding conductor paste of the present disclosure, the adhesive or non-conductive components derived from the adhesive do not inhibit the interaction between conductive particles or between the conductive particles and the substrate, and a conductor wiring or bonded structure having excellent conductivity [electrical resistance value is, for example, 10×10 -6 Ω cm or less, preferably 9.0×10 -6 Ω cm or less, preferably 8.5×10 -6 Ω cm or less, more preferably 7.0×10 -6 It is possible to form a material with a resistivity of less than Ω·cm.
[0124] Furthermore, in the conductor wiring or bonded structure formed on a substrate using the bondable conductor paste of the present disclosure, the conductive particles are densely gathered by sintering and the conductive particles fuse together, thereby enabling the conductive wiring or bonded structure to exhibit excellent bonding strength to the substrate. For example, the bonding strength to a silver-plated copper substrate (in accordance with JIS Z 3198) is 10 MPa or more, preferably 20 MPa or more.
[0125] Since the bonding conductor paste of the present disclosure has the above-mentioned properties, it can be suitably used, for example, for the purpose of producing electronic components (for example, power semiconductor modules, LED modules, etc.) using a printing method. EXAMPLES
[0126] The present disclosure will be described in more detail below based on examples, but the present disclosure is not limited to these examples in any way.
[0127] In the following, the average particle size (median size) of silver particles (A) was measured by the following method. A dispersion of silver particles (A) was observed using a transmission electron microscope (TEM). Observations were made at 100,000x magnification, with 4 fields of view x 50 particles. The observation points were areas where large and small particles coexisted. The number particle size distribution was determined by analyzing the images. This number particle size distribution was converted to a volume particle size distribution using a known conversion formula, assuming that the particles have an aspect ratio of 1. The average particle size (median size) was determined from this particle size distribution.
[0128] The average particle size (median size) of the silver particles (B) is a value measured by a laser diffraction / scattering method.
[0129] The silver particles and solvent used are as follows: [Silver particles (A)] "nAg": Average particle size (median size) 40 nm, manufactured by Daicel Corporation [Silver particles (B)] "AgC-239": Average particle size (median size) 6.0 μm, manufactured by Fukuda Metal Foil & Powder Co., Ltd. "S211A-10": Average particle size (median size) 0.54 μm, manufactured by Daiken Chemical Co., Ltd. [Solvent (Compound (C))] Tripropylene glycol methyl ether: boiling point 242°C, manufactured by Daicel Corporation Dipropylene glycol n-butyl ether: boiling point 229°C, manufactured by Daicel Corporation Dipropylene glycol n-propyl ether: boiling point 212°C, manufactured by Daicel Corporation Tripropylene glycol methyl n-propyl ether: boiling point 258°C, manufactured by Daicel Corporation Diethylene glycol monobutyl ether: boiling point 230℃, manufactured by Daicel Corporation Diethylene glycol monomethyl ether: boiling point 193°C, manufactured by Daicel Corporation Diethylene glycol monoethyl ether: boiling point 196°C, manufactured by Daicel Corporation Diethylene glycol monoethyl ether acetate: boiling point 218°C, manufactured by Daicel Corporation Diethylene glycol monobutyl ether acetate: boiling point 247°C, manufactured by Daicel Corporation Ethylene glycol monobutyl ether acetate: boiling point 192°C, manufactured by Daicel Corporation Ethylene glycol monohexyl ether: boiling point 205°C, manufactured by Daicel Corporation Dipropylene glycol methyl ether acetate: boiling point 213°C, manufactured by Daicel Corporation
[0130] Example 1 50 g of diethylene glycol monobutyl ether was added as a solvent (C1) to 10 g of methanol slurry of nAg, and the mixture was separated into the solvent and wet powder of nAg by centrifugation. The solvent was discarded, and 50 g of diethylene glycol monobutyl ether was added to the wet powder and dispersed, then the wet powder was separated into the solvent and nAg by centrifugation. This operation was repeated three times to obtain a wet powder of diethylene glycol monobutyl ether of nAg. The wet powder was heated to 400°C using TG-DTA, and the weight of diethylene glycol monobutyl ether contained was calculated from the weight loss. The diethylene glycol monobutyl ether content in the wet powder was 14.5 wt%. Then, 80 parts of AgC-239, 23.4 parts of nAg wet powder (20 parts of nAg, 3.4 parts of diethylene glycol monobutyl ether: calculated from the above TG-DTA), and 8 parts of tripropylene glycol methyl n-propyl ether as a solvent (C2) were mixed in a planetary centrifugal mixer to obtain a bonding conductor paste containing nAg and AgC-239.
[0131] Examples 1 to 40 A bonding conductor paste was obtained in the same manner as in Example 1, except that the amounts of silver particles (A), silver particles (B), solvent (C1), and solvent (C2) were as shown in Tables 1 to 6.
[0132] Comparative Example 1 100 parts of AgC-239 and 10 parts of dipropylene glycol n-propyl ether as a solvent (C2) were mixed in a planetary centrifugal mixer to obtain a bonding conductor paste containing AgC-239.
[0133] Comparative Examples 2 to 7 A bonding conductor paste was obtained in the same manner as in Comparative Example 1, except that the amounts of silver particles (B) and solvent (C2) were as shown in Tables 1 to 6.
[0134] (Metal mask printability, bond strength evaluation) The substrates, masks, and equipment used are as follows: [substrate] ·Silver-plated substrate (manufactured by Nippon Test Panel Co., Ltd.) Substrate: Copper (1.0mm x 9mm x 60mm) Base: Electroless nickel plating (5μm) Top surface: Semi-gloss silver plating (1.0 μm) Gold-plated substrate (manufactured by Nippon Test Panel Co., Ltd.) (Examples 32 to 35, Comparative Example 5 only) Substrate: Copper (1.0mm x 9mm x 60mm) Base: Electroless nickel plating (5μm) Top surface: Semi-gloss silver plating (1.0 μm) Silicon chip (manufactured by Yamanaka Hewtech Co., Ltd.) Silicone (0.525mm x 3mm x 3mm) Base: Titanium 500nm sputtered Top surface: Silver 2μm sputtering [mask] Metal mask (manufactured by Towa Tech Co., Ltd.) 3mm x 3mm, mesh thickness 100μm [device] Chip mounter SMT-64H (Okihara Electric Co., Ltd.) Sintering furnace (reflow furnace) RSS-450-210-FA (UNITEMP)
[0135] The bonding conductive paste obtained in the above Examples and Comparative Examples was applied to a substrate (1) by a metal mask printing method to form a coating film (coating film thickness: about 100 μm). The metal mask printability was evaluated according to the following criteria. The results are shown in Tables 1 to 4. · The coating film does not bleed out from the substrate, whether it is silver-plated substrate, gold-plated substrate, or silicon chip substrate. · Good The coating film seeps out of the substrate on either the silver-plated substrate, the gold-plated substrate, or the silicon chip.
[0136] Next, a substrate (2) identical to the substrate (1) was placed on the formed coating film, and the substrate was heated and sintered in a reflow furnace under the following conditions to produce a sample (substrate (1) / sintered bondable conductor paste / substrate (2)). Under air (Examples 1 to 35, 40, Comparative Examples 1 to 5, 7): 25℃→180℃ (heating rate: 15℃ / min) Hold at 180℃ for 60 minutes Under air (Examples 36 to 39, Comparative Example 6) 25℃→160℃ (heating rate: 15℃ / min) Hold at 160℃ for 60 minutes Under nitrogen atmosphere (Examples 1 to 31, Comparative Examples 1 to 4): 25℃→250℃ (heating rate: 15℃ / min) Hold at 250℃ for 60 minutes Under nitrogen atmosphere (Example 40, Comparative Example 7) 25℃→180℃ (heating rate: 15℃ / min) Hold at 180℃ for 60 minutes
[0137] For the obtained samples (n=4), the bond strength between the substrate (1) and the substrate (2) was measured and the bondability was evaluated under the following conditions at room temperature using a die shear tester SERIES4000 (manufactured by DAGE). The average values of the bond strength (MPa) when a silver-plated substrate, a gold-plated substrate (only Examples 32 to 35 and Comparative Example 5) and a silicon chip were used as the substrate are shown in Tables 1 to 5. Test speed: 50μm / s Test height: 50μm
[0138] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5]
[0139] The bonding conductor paste of the Example containing silver particles (A) had good mask printability, whereas the bonding conductor paste of the Comparative Example not containing silver particles (A) had poor mask printability. In addition, the bonding strength of the bonding conductor paste of the Comparative Example not containing silver particles (A) was significantly reduced in a nitrogen atmosphere, whereas the bonding conductor paste of the Example containing silver particles (A) showed good bonding strength even in a nitrogen atmosphere.
[0140] The bonding strength of the bonding conductive pastes of Example 40 and Comparative Example 7 was evaluated in the same manner as above, except that the sintering time (hold time) was 10 minutes, 20 minutes, 30 minutes, and 60 minutes. The results are shown in Table 6. [Table 6]
[0141] The bonding conductor paste of the Example containing silver particles (A) showed good bonding strength even when the sintering time was shortened, whereas the bonding conductor paste of the Comparative Example not containing silver particles (A) showed a large decrease in bonding strength even in air when the sintering time was shortened.
[0142] Each feature disclosed herein may be combined with any other feature disclosed herein. Each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited to the embodiments, but is limited only by the scope of the claims.
[0143] Variations of the present disclosure described above are noted below. [1] A bonding conductor paste for forming a conductor wiring and / or a bonded structure for connecting electronic elements, comprising conductive particles and a solvent, the conductive particles including silver particles (A) having an average particle diameter of 1 nm or more and less than 100 nm and silver particles (B) having an average particle diameter of 0.1 μm or more and 10 μm or less, The silver particles (A) are silver nanoparticles whose surfaces are coated with a protective agent containing an amine, As a solvent, R a -O-(XO) n -R b (I) (In the formula, R a represents a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. X represents a divalent group selected from a hydrocarbon group having 2 to 6 carbon atoms. R b R represents a hydrogen atom or a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. a and R b may be the same group. n represents an integer of 1 to 3. A bonding conductor paste comprising a compound (C) represented by the formula: [2] The bondable conductor paste according to the above [1], wherein the silver particles (A) have an average particle size (median size) of 0.5 to 90 nm (preferably 1 to 80 nm, and more preferably 1 to 75 nm). [3] The bonding conductor paste according to the above [1] or [2], wherein the proportion of silver particles (A) among all silver particles contained in the bonding conductor paste is 50% by weight or less (preferably 45% by weight or less, more preferably 40% by weight or less). [4] The bonding conductor paste according to any one of the above [1] to [3], wherein the proportion of silver particles (A) among all silver particles contained in the bonding conductor paste is 1 wt % or more (preferably 3 wt % or more, more preferably 4 wt % or more). [5] The bonding conductor paste according to any one of the above [1] to [4], wherein the content of the silver particles (A) is 1 to 45% by weight (preferably 2 to 43% by weight, more preferably 3 to 40% by weight) relative to the total amount of the bonding conductor paste (100% by weight). [6] The protective agent in the silver particles (A) contains, as an amine, an aliphatic hydrocarbon monoamine (1) which comprises an aliphatic hydrocarbon group and one amino group, and the total number of carbon atoms in the aliphatic hydrocarbon group is 6 or more, The bonding conductor paste according to any one of the above [1] to [5] further contains at least one of an aliphatic hydrocarbon monoamine (2) consisting of an aliphatic hydrocarbon group and one amino group, the total number of carbon atoms of the aliphatic hydrocarbon group being 5 or less, and an aliphatic hydrocarbon diamine (3) consisting of an aliphatic hydrocarbon group and two amino groups, the total number of carbon atoms of the aliphatic hydrocarbon group being 8 or less. [7] The proportion of the aliphatic hydrocarbon monoamine (1) to either one or both of the aliphatic hydrocarbon monoamine (2) and the aliphatic hydrocarbon diamine (3) is, based on the total amines [(1) + (2) + (3)], The aliphatic monoamine (1): 5 mol% to 65 mol% Total amount of the aliphatic monoamine (2) and the aliphatic diamine (3): 35 mol % to 95 mol % The bonding conductor paste according to the above [6], [8] When the aliphatic monoamine (1) is used in combination with both the aliphatic monoamine (2) and the aliphatic diamine (3), the proportions of the aliphatic monoamine (1) and the aliphatic diamine (3) used are, based on the total amines [(1) + (2) + (3)], The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic monoamine (2): 5 mol% to 70 mol% The aliphatic diamine (3): 5 mol% to 50 mol% The bonding conductor paste according to the above [6], [9] When the aliphatic monoamine (1) and the aliphatic monoamine (2) are used (without the aliphatic diamine (3)), the proportion of them used is, based on the total amines [(1) + (2)], The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic monoamine (2): 35 mol% to 95 mol% The bonding conductor paste according to the above [6],
[10] When the aliphatic monoamine (1) and the aliphatic diamine (3) are used (without the aliphatic monoamine (2)), the proportion of them used is, based on the total amines [(1) + (3)], The aliphatic monoamine (1): 5 mol% to 65 mol% The aliphatic diamine (3): 35 mol% to 95 mol% The bonding conductor paste according to the above [6],
[11] The bondable conductor paste according to any one of the above [1] to
[10] , wherein the protective agent further contains an aliphatic carboxylic acid (4).
[12] The bonding conductor paste according to the above
[11] , wherein the aliphatic carboxylic acid (4) includes a saturated or unsaturated aliphatic monocarboxylic acid having 8 to 18 carbon atoms.
[0144]
[13] The bondable conductor paste according to any one of the above [1] to
[12] , wherein the silver particles (B) have an average particle size (median size) of 0.1 to 9 μm (preferably 0.3 to 8 μm).
[14] The specific surface area of the silver particles (B) is 0.5 to 4.0 m2 / g (preferably 0.6 to 3.0 m 2 / g, more preferably 0.7 to 2.5 m 2 / g, more preferably 0.8 to 2.5 m 2 / g).
[15] The bonding conductor paste according to any one of the above [1] to
[14] , wherein the proportion of silver particles (B) among all silver particles contained in the bonding conductor paste is 40% by weight or more (preferably 50% by weight or more, more preferably 60% by weight or more).
[16] The bonding conductor paste according to any one of the above [1] to
[15] , wherein the proportion of silver particles (B) among all silver particles contained in the bonding conductor paste is 99% by weight or less (preferably 97% by weight or less, more preferably 95% by weight or less).
[17] The bonding conductor paste according to any one of the above [1] to
[16] , wherein the silver particles (B) include silver particles (group) having an average particle diameter of 0.1 to 1.5 μm (preferably 0.1 to 0.6 μm) and silver particles (group) having an average particle diameter of more than 1.5 μm and 8 μm or less (preferably 5 to 8 μm).
[18] The bonding conductor paste according to the above item
[17] , wherein the ratio (former / latter: weight ratio) of the silver particles (group) having an average particle diameter of 0.1 to 1.5 μm to the silver particles (group) having an average particle diameter of more than 1.5 μm and 8 μm or less is 70 / 30 to 30 / 70 (preferably 40 / 60 to 60 / 40, and more preferably 45 / 55 to 55 / 45).
[19] The bonding conductor paste according to any one of the above [1] to
[18] , wherein the content of the silver particles (B) is 20 to 95% by weight (preferably 30 to 90% by weight, and more preferably 40 to 90% by weight) relative to the total amount of the bonding conductor paste (100% by weight).
[0145]
[20] The bondable conductor paste according to any one of the above [1] to
[19] , wherein the boiling point of the compound (C) represented by the formula (I) under normal pressure is 160°C or higher (preferably 190°C or higher, more preferably 190 to 290°C, and even more preferably 200 to 260°C).
[21] The SP value at 25°C of the compound (C) represented by the formula (I) [(cal / cm 3 ) 1 / 2 The bondable conductor paste according to any one of the above [1] to
[20] , wherein the value of [Ratio of viscosity of the bonded conductor] is 11.0 or less (preferably 10.0 or less, more preferably 9.0 or less).
[22] The bondable conductor paste according to any one of the above [1] to
[21] , wherein X in the formula (I) is an ethylene group, a propylene group or a trimethylene group.
[23] The bonding conductor paste according to any one of the above [1] to
[22] , wherein the content of the compound (C) represented by formula (I) in the total amount of the solvent (100% by weight) is 70 to 100% by weight (preferably 80% by weight to 100% by weight, more preferably 85% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, even more preferably 95% by weight to 100% by weight, and even more preferably 99% by weight to 100% by weight).
[24] The bonding conductor paste according to any one of the above [1] to
[23] , wherein the content of the compound (C) represented by formula (I) is 1 to 50 parts by weight (preferably 2 to 30 parts by weight, and more preferably 3 to 30 parts by weight) per 100 parts by weight of the conductive particles (total of silver particles (A) and silver particles (B)).
[0146]
[25] A bonding conductor paste according to any one of the above [1] to
[24] , wherein the content of the solvent (the total content when two or more types are contained) in the total amount of the bonding conductor paste (100% by weight) is 1 to 50% by weight (preferably 2 to 40% by weight, more preferably 3 to 30% by weight).
[26] A bonding conductor paste according to any one of the above [1] to
[25] , wherein the content of the compound (C) represented by formula (I) in the total amount (100 wt%) of the bonding conductor paste (the total content when two or more types are contained) is 1 to 50 wt% (preferably 2 to 40 wt%, more preferably 3 to 30 wt%).
[27] A bonding conductor paste according to any one of the above [1] to
[26] , wherein the content of conductive particles in the total amount of the bonding conductor paste (100% by weight) (the total content when two or more types are contained) is 50 to 99% by weight (preferably 60 to 97% by weight, more preferably 70 to 95% by weight).
[28] The bonding conductor paste according to any one of the above [1] to
[27] , wherein the total content of the silver particles (A) and the silver particles (B) in the total amount (100 wt%) of the bonding conductor paste is 50 to 99.8 wt% (preferably 60 to 97 wt%, more preferably 70 to 95 wt%).
[29] A bonding conductor paste according to any one of the above [1] to
[28] , wherein the combined content of the compound (C) represented by formula (I) and silver particles in the total amount of the bonding conductor paste (100% by weight) is 70% by weight or more (preferably 80% by weight or more, and more preferably 90% by weight or more).
[30] The bonding conductor paste according to any one of the above [1] to
[29] , wherein the content of the organic component is 15% by weight or less (preferably 13% by weight or less) relative to the bonding conductor paste (100% by weight).
[31] The bonding conductor paste according to any one of the above [1] to
[30] , wherein the content of the adhesive (e.g., a polymeric compound having a molecular weight of 10,000 or more, such as an epoxy resin, a silicone resin, or an acrylic resin) is 10% by weight or less (preferably 5% by weight or less, more preferably 1% by weight or less, and even more preferably 0.5% by weight or less) of the total amount (100 weight) of the bonding conductor paste.
[32] A method for producing an electronic component, comprising the steps of applying the bonding conductor paste according to any one of the above [1] to
[31] onto a substrate, and then sintering the paste to form a conductor wiring and / or a bonded structure. [Industrial Applicability]
[0147] The bonding conductor paste of the present disclosure can be suitably used, for example, for the purpose of producing electronic components (such as power semiconductor modules, LED modules, etc.) using a printing method.
Claims
1. A bonding conductor paste for forming a conductor wiring and / or a bonded structure for connecting electronic elements, comprising conductive particles and a solvent, the conductive particles including silver particles (A) having an average particle diameter of 1 nm or more and less than 100 nm and silver particles (B) having an average particle diameter of 0.1 μm or more and 10 μm or less, The silver particles (A) are silver nanoparticles having a configuration in which the surfaces are coated with a protective agent containing an amine, As a solvent, R a -O-(X-O) n -R b (I) (In the formula, R a represents a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. X represents a divalent group selected from a hydrocarbon group having 2 to 6 carbon atoms. R b R represents a hydrogen atom or a monovalent group selected from a hydrocarbon group having 1 to 6 carbon atoms and an acyl group. a and R b may be the same group; n is 3. The compound (C) is represented by A conductive paste in which the content of organic components including the solvent is 15% by weight or less relative to the conductive paste (100% by weight).
2. The bonding conductor paste according to claim 1 , wherein the proportion of silver particles (A) in all silver particles contained in the bonding conductor paste is 50% by weight or less.
3. the protective agent in the silver particles (A) contains, as an amine, an aliphatic hydrocarbon monoamine (1) which is composed of an aliphatic hydrocarbon group and one amino group, and the total number of carbon atoms in the aliphatic hydrocarbon group is 6 or more, 3. The adhesive conductor paste according to claim 1 or 2, further comprising at least one of an aliphatic hydrocarbon monoamine (2) comprising an aliphatic hydrocarbon group and one amino group, the total number of carbon atoms of the aliphatic hydrocarbon group being 5 or less, and an aliphatic hydrocarbon diamine (3) comprising an aliphatic hydrocarbon group and two amino groups, the total number of carbon atoms of the aliphatic hydrocarbon group being 8 or less.
4. The bondable conductor paste according to any one of claims 1 to 3, wherein the compound (C) represented by the formula (I) has a boiling point of 160°C or higher under normal pressure.
5. The SP value at 25° C. of the compound (C) represented by the formula (I) [(cal / cm 3 ) 1/2 5. The conductive paste according to claim 1, wherein the value of [R] is 11.0 or less.
6. 6. The bondable conductor paste according to claim 1, wherein X in formula (I) is an ethylene group, a propylene group, or a trimethylene group.
7. The bonding conductor paste according to any one of claims 1 to 6, wherein the total content of the silver particles (A) and the silver particles (B) in the total amount of the bonding conductor paste is 50 to 99.8% by weight.
8. A method for producing an electronic component, comprising the steps of applying the bonding conductor paste according to any one of claims 1 to 7 onto a substrate, and then sintering the applied paste to form a conductor wiring and / or a bonded structure.
9. A bonding conductor paste for forming a conductor wiring and / or a bonding structure for connecting electronic elements, comprising conductive particles and a solvent, the conductive particles including silver particles (A) having an average particle diameter of 1 nm or more and less than 100 nm and silver particles (B) having an average particle diameter of 0.1 μm or more and 10 μm or less, The silver particles (A) are silver nanoparticles having a configuration in which the surfaces are coated with a protective agent containing an amine, As a solvent, R a -O-(X-O) n -R b (I) (In the formula, R a represents a monovalent group selected from a hydrocarbon group and an acyl group having 1 to 6 carbon atoms. X represents a divalent hydrocarbon group having 3 carbon atoms. R b represents a hydrogen atom or a monovalent group selected from a hydrocarbon group and an acyl group having 1 to 6 carbon atoms. R a and R b may be the same group. n represents an integer of 1 to 3.) The compound (C) is represented by A conductive paste in which the content of organic components including the solvent is 15% by weight or less relative to the conductive paste (100% by weight).
Citation Information
Patent Citations
Conductive paste
JP2009170277A
Silver particle coating composition
WO2015163076A1
Conductive paste
WO2017038572A1